QUANTIFYING WATERSCAPE DESIGN IMPACT ON URBAN VISITOR PSYCHOLOGY IN DENPASAR - Prasandya, Km Deddy Endra; Satria, Made Wina (Border: Jurnal Arsitektur, 2025)
Urban public spaces enhanced with waterscape features offer notable benefits for psychological well-being, particularly through multisensory and spatial engagement. Although theoretical frameworks on healing waterscapes have gained attention, empirical research examining user perceptions within real-world urban settings remains limited. This study investigates how visitors perceive four psychological variables of waterscape design (social, behavioral, cognitive, and emotional) in a prominent public space in Denpasar, Bali. Data were collected through a structured questionnaire, developed from established design sub-criteria, and distributed to visitors at Lapangan Puputan Badung. Responses were analyzed using JMP software to explore perceptual trends across the four variables. Findings indicate that emotional and behavioral aspects received the highest perception scores. Elements such as natural vegetation, organic materials, and ambient natural sounds like rustling leaves, bird songs, and flowing water were strongly associated with feelings of comfort, calmness, and restoration. On the other hand, social and cognitive aspects, including opportunities for interaction, spatial legibility, and acoustic clarity, were rated lower, suggesting areas where the current design may not fully support psychological needs. These insights highlight a perceptual imbalance in the spatial experience of the site. The study contributes practical implications for urban designers and landscape architects in enhancing the restorative qualities of waterscape environments.